Memory of Central and Eastern Europe : past traumas, present challenges, future horizons - Marková, Alena HerausgeberIn; Kuznetcova, Mariia HerausgeberIn (Charles University, Karolinum Press, 2023)
This volume provides a unique platform for collaboration of different theoretical and conceptual approaches to memory and related studies. The first part of the book focuses on the issues related to the problematic aspects of memory in the context of urban and media space. The second part deals with the interaction between nation, national history and memory. The third part is devoted to the representation of memory and sheds light on the specific role of text as a means of cultural memory.